Determinasi Pertumbuhan Ekonomi Dan Tingkat Pengangguran Terbuka Terhadap Kemiskinan Di Kabupaten Tulungagung - Nafik Umurul Hadi; Slamet Pamuji (Journal on Education, 2024)
The research aims to determine the impact of economic growth and open unemployment rates on poverty in Tulungagung district in 2009 to 2022. The research method is a type of descriptive quantitative research using double linear regression analysis and data with data used such as macro data of economic growth, open unemployment, and poverty of districts of Tulungagung which originates from BPS Tulungabung. The results of the study showed that economic growth had a significant negative (reversible) impact on poverty with a count t value > t table (-14,985 > 1,795) and a significant 0,000 > 0,05. Open unemployment had no significant impact on Poverty with the count T value < T table (1,278 < 1,795), and significant 0.228 > 0.05.